EP388 Laparoscopic para-aortic lymph node staging in the care of advanced cervical cancer (IB3-IVA): retroperitoneal or transperitoneal?. (1st November 2019) - Pécout, M; Bourgin, C; Azais, H; Machuron, F; Nyangoh Timoh, K; Oulmader, L; Canlorbe, G; Coutant, C; Graesslin, O; Touboul, C; Bricou, A; Huchon, C; et al.
Abstract : Introduction/Background: Para-aortic lymphadenectomy is currently not systematized in the pre-treatment management of advanced cervical cancer (FIGO IB3-IVA). However, metastatic lymph has prognostic and therapeutic importance. We compared morbidity and mortality of retroperitoneal para-aortic lymphadenectomy with transperitoneal approach, in the pre-therapeutic lymph node staging of cervix cancers at a locally advanced stage (FIGO IB3-IVA). Methodology: All pre- and postoperative data from 331 patients operated for advanced cervical cancer with a negative Positron Emission Tomography-scanner, managed between 1999 and 2017 in 9 centers in France were listed in the FRANCOGYN database. Morbidity and mortality related to the surgical approach was assessed by studying the rate of per and postoperative complications, as well as the duration of hospitalization. Also analyzed were overall survival as well as survival without recurrence. Results: 164 patients received a retroperitoneal approach (group 1) and 167 patients received a transperitoneal approach (group 2). Of these 331 patients, 12 had an intraoperative complication (4 of group 1 and 8 of group 2, p=0.36) and 34 a postoperative complication (12 of group 1 and 22 of group 2, p=0.044), none of which required surgical revision. Hospital stay was shorter in group 1 than in group 2 (3.87±2.47 days versus 5.17±3.04 days, p<0.001). There was no significant difference in mortality between the two groups; 25 patients in group 1 died (15.24%), compared with 26 patients in group 2 (15.57%). There was no significant difference in recidivism; 40 patients in group 1 had a recurrence (24.39%), compared with 37 in group 2 (22.16%). Conclusion: The transperitoneal approach has more complications postoperatively and a longer hospital stay than the retroperitoneal approach. In contrast, there is no significant difference in survival without recurrence or overall survival depending on the approach. Disclosure: Nothing to disclose.